2010
DOI: 10.1016/j.biomaterials.2010.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of topographical effects on macrophage behavior in a foreign body response model

Abstract: Current strategies to limit macrophage adhesion, fusion and fibrous capsule formation in the foreign body response have focused on modulating material surface properties. We hypothesize that topography close to biological scale, in the micron and nanometric range, provides a passive approach without bioactive agents to modulate macrophage behavior. In our study, topography-induced changes in macrophage behavior was examined using parallel gratings (250 nm-2 μm line width) imprinted on poly(s-caprolactone) (PCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
327
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(344 citation statements)
references
References 68 publications
16
327
1
Order By: Relevance
“…The immune response to tissue-engineered scaffold materials is critical to their success, and as such, investigators have explored whether physical factors, such as substrate topology, influence macrophage behavior. Interestingly, it has been observed that surface features indeed affect macrophage morphology and cytokine secretion profiles (31)(32)(33), as well as the overall and fibrotic responses (34), although the mechanisms underlying these responses have so far remained elusive. Our data suggest that topological cues might lead to different macrophage responses by influencing their shape and cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to tissue-engineered scaffold materials is critical to their success, and as such, investigators have explored whether physical factors, such as substrate topology, influence macrophage behavior. Interestingly, it has been observed that surface features indeed affect macrophage morphology and cytokine secretion profiles (31)(32)(33), as well as the overall and fibrotic responses (34), although the mechanisms underlying these responses have so far remained elusive. Our data suggest that topological cues might lead to different macrophage responses by influencing their shape and cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The solution was loaded into 10 mL Luer-lock syringe with 25-gauge needle, and the infusion rate was regulated by a syringe pump (Harvard PHD syringe pump, Harvard Apparatus, Holliston, MA, USA). The infusion rate was set to 1 mL/h; the distance between the needle tip and steel mash collector was 18 cm.…”
Section: Pcl Nanofibrous Mesh Preparation and Tensile Testmentioning
confidence: 99%
“…28,29 With the decrease in intracapsular pressure, the neoformed tissue induced by a chamber undergoes further expansion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…electrospun polymeric fibres, extruded collagen fibres and isoelectrically focused collagen fibres) have been shown to maintain tenocyte phenotype and to differentiate stem cells towards tenogenic lineage in vitro and to induce acceptable regeneration in preclinical models, none of these technologies offers precise control over the spatial distribution of the fibres. Imprinting technologies, on the other hand, have demonstrated a diverse effect on a range of permanently differentiated and stem cell functions, including adhesion, orientation, secretome expression and lineage commitment [41][42][43][44][45][46][47][48] and offer significantly greater control over feature dimension and spacing. Specifically to tendon repair, such technologies have been shown to maintain tenocyte phenotype [38]; to promote aligned tendon-specific ECM deposition [39]; and to differentiate stem cells towards tenogenic lineage [40].…”
Section: Introductionmentioning
confidence: 99%